Tropical forests & global atmospheric change - Malhi, Y. (Yadvinder).; Phillips, Oliver (Oxford New York Oxford University Press, 2005)
This text explores the vigorous contemporary debate as to how rapidly tropical forests may be affected by atmospheric change, and what this may mean for their future.
change and speciation in neotropical seasonally dry forest plants / R. Toby Pennington, Matt Lavin -- The prospects for tropical forests in the twenty-first-century atmosphere / Oliver L. Phillips and Yadvinder Malhi.
Includes bibliographical references (p. 227-249) and index.
Keywords: Climatic changes -- Tropics; Forest ecology -- Tropics; Forest microclimatology -- Tropics; Biodiversity -- Climatic factors -- Tropics; Electronic books; Electronic books